Case Report: “DEK::AFF2 fusion associated sinonasal carcinomas: a novel oncogenic driver and emerging therapeutic strategies” - Moritz Knebel; Moritz Knebel; Abbas Agaimy; Jan Philipp Kühn; Jan Philipp Kühn; Sandrina Körner; Sandrina Körner; Felix Braun; Felix Braun; Lukas Brust; Lukas Brust; Veronika Flockerzi; et al. (Frontiers in Immunology, 2025)
BackgroundDEK::AFF2 fusion-associated carcinomas of the sinonasal tract are exceedingly rare, with fewer than 100 cases reported worldwide, but probably underrecognized. Recently classified by the WHO as a distinct provisional subtype of non-keratinizing squamous cell carcinoma, these tumors pose significant diagnostic and therapeutic challenges. Their histological resemblance to inverted papillomas and their bland histology in most cases often leads to misdiagnosis, while their aggressive behavior underscores the need for a tailored treatment approach.Case presentationWe report two cases of DEK::AFF2 fusion-associated carcinomas managed at Saarland University Medical Center. The first case involved a 46-year-old woman who initially presented with recurrent sinonasal inverted papilloma, confirmed through multiple surgical interventions over nearly a decade. In 2023, reevaluation and genetic analysis revealed a DEK::AFF2 fusion. The patient demonstrated an exceptional response to three cycles of neoadjuvant gemcitabine and cisplatin, achieving complete remission on MRI restaging. This allowed a shift to definitive chemoradiotherapy, with sustained disease-free status confirmed by a PET-CT three months post-treatment in July 2024. The second case involved a 66-year-old woman presenting with recurrent inverted papilloma affecting the sinonasal and tympanic regions. Despite multiple surgeries, malignant transformation to invasive squamous cell carcinoma occurred, with lymph node metastasis and intracranial spread. A combined otolaryngological and neurosurgical approach was undertaken, but the disease progressed. The patient passed away in January 2020, with postmortem review of the prior histology and genetic analysis confirming DEK::AFF2 fusion carcinoma that showed bland-looking papilloma-like morphology in the initial specimens and later a high-grade cytology indicating biological progression to poorly differentiated carcinoma.ConclusionThese cases highlight the aggressive nature of DEK::AFF2 fusion-associated carcinomas and the critical role of genetic profiling in diagnosis and management. The exceptional, first ever reported response to neoadjuvant chemotherapy in one case underscores the potential for personalized treatment strategies, warranting further investigation into targeted therapies for this rare malignancy.